CPA Examination: Accounting Practice. - Chamberlain, John H. (The Accounting Review, 1966)
The article presents a question paper prepared by the Board of Examiners of the American Institute of Certified Public Accountants which was presented in the 1st half of the Certified Public Accountants (CPA) examination in accounting practice on May 18, 1966. The candidates were required to solve all the problems. All the questions were grouped into five sections. The suggested time allowances for each section was fixed at 40 to 50 and 50 to 60 minutes. Section 1 comprised of 20 multiple choice questions. Section 2 presented a question which required students to prepare a financial statement and to compute income-tax liability. Section 3 required the students to prepare a schedule to compute minimum bid i.e., the bid that would neither increase nor decrease total profits. Section 4 asked of students to prepare a formal consolidated statement of source and application of funds for a company and its subsidiary and a formal schedule of changes in consolidated working capital. Questions in section 5 required students to compute gross profit margin.